The Labyrinth of time the illusion of past, present and future - Peake, Anthony (Arcturus Pub. Limited, 2012)
Time is the greatest of all mysteries. In The Labyrinth of Time, author Tony Peake seeks to come to an understanding of its elusive nature. Drawing on a remarkable breadth of philosophy, quantum physics, theology, cosmology, neurology, psychiatry and even popular culture to explore the relationship between consciousness and our subjective experiences of time, he sets out an amazing theory that will change forever the way you view your life.